2022
DOI: 10.3389/fnins.2022.944709
|View full text |Cite
|
Sign up to set email alerts
|

Iron deposition in the precuneus is correlated with mild cognitive impairment in patients with cerebral microbleeds: A quantitative susceptibility mapping study

Abstract: PurposeThe purpose of this study was to define whether mild cognitive impairment (MCI) is associated with iron deposition in rich-club nodes distant from cerebral microbleeds (CMBs) in patients with cerebral small vessel disease (CSVD).MethodsA total of 64 participants underwent magnetic resonance imaging (MRI) scanning and were separated into three groups, namely, CMB(+), CMB(–), and healthy controls (HCs). We compared their characteristics and susceptibility values of rich-club nodes [e.g., superior frontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…QSM patterns are likely different in patients with SVD caused by cerebral amyloid angiopathy, which is expected to show paramagnetic susceptibility signal both due to iron colocalized with vascular deposits of amyloid, as described above, and due to microhemorrhages that result from CAA ( Charidimou et al, 2012 ). QSM-MRI is highly sensitive to such cortical microbleeds, even more so than T2* signal, and in combination with FDG-PET can reveal differential etiology of SVD and its impact on brain vascular function ( Lee et al, 2022 ; Tu et al, 2022 ).…”
Section: Mechanism-based Review Of Qsm-pet Comparisonsmentioning
confidence: 99%
“…QSM patterns are likely different in patients with SVD caused by cerebral amyloid angiopathy, which is expected to show paramagnetic susceptibility signal both due to iron colocalized with vascular deposits of amyloid, as described above, and due to microhemorrhages that result from CAA ( Charidimou et al, 2012 ). QSM-MRI is highly sensitive to such cortical microbleeds, even more so than T2* signal, and in combination with FDG-PET can reveal differential etiology of SVD and its impact on brain vascular function ( Lee et al, 2022 ; Tu et al, 2022 ).…”
Section: Mechanism-based Review Of Qsm-pet Comparisonsmentioning
confidence: 99%
“…The magnetic resonance imaging (MRI) from the affected patient showed that the affected region had a high iron quantity [ 220 ]. In comparison to a normal individual, an AD patient with mild cognitive dysfunction showed a higher amount of Fe along with an elevated Aβ plaque load in the cortical region that elevated the chances of AD [ 221–223 ]. Numerous investigators showed that an imbalance of iron in brain homeostasis is associated with Aβ plaques and NFTs [ 219 ].…”
Section: Neurological Diseases Associated With Signaling Pathways Of ...mentioning
confidence: 99%